“There is a Time for Departure Even when There’s no Certain Place to Go”: the Twisting Path to Selfhood and Adulthood - Pivoriūtė, Milda (Sociologija. Mintis ir veiksmas, 2021)
In today’s post-industrial societies, young people, compared to previous generations, experience longer and more complex processes of creating professional identity, developing a career or finding “one’s vocation”. They also face difficulties in achieving financial independence, starting a family, and leaving parental homes, which altogether define the status of an adult person. Based on the overview of sociological and psychological scholarly literature, the complexity of young people’s identity formation in the context of a passage towards social maturity is analysed. The most significant tensions related to the question of “who am I and what do I want” are emphasized in the article, together with the circumstances of contemporary society that stimulate them. (Non-)applicability of the concept of the quarter-life crisis is finally highlighted in order to summarise, reflect, and explain some of the experiences and life events of young people. The title of the article is a famous quotation of Tennessee Williams.